2010
DOI: 10.1038/jid.2009.409
|View full text |Cite
|
Sign up to set email alerts
|

A Prevalent Mutation with Founder Effect in Xeroderma Pigmentosum Group C from North Africa

Abstract: Xeroderma pigmentosum (XP) is a rare autosomal recessive disorder that is associated with an inherited defect of the nucleotide excision repair pathway (NER). In this study, we investigated the involvement of XP genes in 86 XP patients belonging to 66 unrelated families, most of them consanguineous and originating from Maghreb. Sequencing analysis was performed either directly (44 probands) or after having previously characterized the involved XP gene by complementation assay (22 families). XPC and XPA mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
146
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(162 citation statements)
references
References 29 publications
11
146
1
4
Order By: Relevance
“…13 The c.1643_1644delTG mutation in the XPC gene represents the major cause of xeroderma pigmentosum in Maghreb region (Morocco, Algeria and Tunisia); haplotype analysis revealed the presence of a common founder effect for this XPC mutation in the Mediterranean region. 14,15 The identification of founder mutations has important implications in molecular diagnosis and genetic counselling. Furthermore, a few prevalent founder mutations enable human geneticists to make more efficient genetic screening than testing for many rare mutations.…”
Section: Discussionmentioning
confidence: 99%
“…13 The c.1643_1644delTG mutation in the XPC gene represents the major cause of xeroderma pigmentosum in Maghreb region (Morocco, Algeria and Tunisia); haplotype analysis revealed the presence of a common founder effect for this XPC mutation in the Mediterranean region. 14,15 The identification of founder mutations has important implications in molecular diagnosis and genetic counselling. Furthermore, a few prevalent founder mutations enable human geneticists to make more efficient genetic screening than testing for many rare mutations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of XP patients in northern Africa reported a founder mutation in one of the DNA repair genes (XPC) [3] . This raises the possibility for XP genetic screening in certain high-risk ethnic groups likely to carry this mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos realizados na década de 70, através da fusão de células proficientes e deficientes e análise da capacidade da célula fusionada de complementar o defeito no reparo (Weerd-Kastelein et al, 1972), e posteriormente com a clonagem dos genes na década de 90, determinaram-se sete grupos de complementação denominados XP-A até XP-G que apresentam defeitos em NER (De Boer e Hoeijmakers, 2000), e um oitavo grupo denominado XP-V (XP variante), que é proficiente em NER e apresenta mutações na polimerase TLS  (pol eta ou POLH), importante na síntese de DNA na presença de fotolesões (Johnson et al, 1999;Masutani et al, 1999). A incidência de XP varia de acordo com a região, sendo de 1:450.000 na Europa e nos Estados Unidos (Kleijer et al, 2008), podendo aumentar para aproximadamente 1:20.000 em algumas regiões como o Japão, onde há um forte efeito fundador de mutações em XPA (Hirai et al, 2006), no norte da África, com prevalência de mutações em XPC (Soufir et al, 2010), e no centro do Brasil, onde há uma população com grande incidência de mutações em XPV (Chaibub, 2013).…”
Section: Xeroderma Pigmentosum (Xp)unclassified
“…A linhagem XPCS2 apresenta somente um alelo funcional do gene XPD, que carrega uma substituição G→A no nucleotídeo 1805, resultando na mudança do aminoácido glicina para aspartato no códon 602 (G602D) na proteína (Takayama et al, 1995)  AS66Las/TTD2VI (TTD/XPD): linhagem de fibroblasto de pele obtida a partir de biópsia de uma paciente de 4 anos de idade, com sintomas típidos de TTD: retardo mental, baixo peso e estatura, ictiose, e cabelos e pêlos curtos e quebradiços (Sarasin et al, 1992). Essa linhagem foi transformada em 1995 por Eveno et al, e possui uma substituição de arginina para prolina em homozigose no códon 592 (R592P) (Nishiwaki et al, 2004)  XP30RO-SV (XP-V): linhagem estabelecida a partir de uma biópsia de pele de um paciente de 30 anos, transformada em 1999 por Cleaver et al Essa linhagem possui uma deleção em homozigose próxima à extremidade 5' do gene POLH (del343-355), causando um frameshift e levando à síntese de uma proteína truncada, de aproximadamente 42 aminoácidos (Masutani et al, 1999)  XP189VI (XP-C): linhagem de fibroblastos primários estabelecida a partir de biópsia de uma paciente do norte de África, portando em homozigose a mutação em frameshift c.1643_1644delTG (p.Val548AlafsX25) no gene XPC, o que leva à produção de uma proteína truncada (Soufir et al, 2010)  FHN: linhagem de fibroblastos primários estabelecida a partir de biópsia de pele realizada no Hospital das Clínicas (FM-USP) de um paciente sem sintomas de XP.…”
Section: Linhagens Celularesunclassified
See 1 more Smart Citation